Aromatase inhibitors in puberty. (October 2020) - Hero, Matti; Varimo, Tero; Raivio, Taneli
Abstract: Sex steroids play an important role in regulating postnatal growth. The interplay between androgens and estrogens is mediated through the activity of aromatase enzyme, which catalyzes the synthesis of estrogens from androgens. Aromatase inhibitors (AIs) are compounds that block the function of the enzyme resulting in depletion of estrogens. In men, estrogens induce pubertal growth spurt and closure of epiphyseal plates, and thus contribute to the attainment of adult height. After loosening of the central restrain of puberty, estrogens in the large part mediate the negative feedback to the hypothalamus and pituitary, and thus control the activity of the hypothalamic–pituitary–gonadal axis. Consequently, AIs have been used in adolescent boys to treat idiopathic short stature and delayed puberty. In this article, we review the published data on the impact of potent 3rd generation AIs on gonadal function and growth in pubertal boys.